Relationship between maternal caffeine and coffee intake and pregnancy loss: A grading of recommendations assessment, development, and evaluation-assessed, dose-response meta-analysis of observational studies - Jafari, Alireza; Naghshi, Sina; Shahinfar, Hossein; Salehi, Sayed Omid; Kiany, Fateme; Askari, Mohammadreza; Surkan, Pamela J.; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Background Numerous studies report an association between coffee or caffeine consumption and pregnancy loss; however, the nature and strength of this relationship have not been clearly established. Based on recent studies, our meta-analysis aimed to test whether a dose–response relationship between coffee or caffeine consumption and pregnancy loss exists. Methods We searched for articles in PubMed, Web of Science, and Scopus published until May 2022. Two independent reviewers extracted data and rated the quality of the evidence using the GRADE approach. We applied a random-effects, one-stage dose–response meta-analysis. Results A total of 34 articles (18 cohort studies and 16 case-control studies) were included in this review. Results showed a significantly higher risk of pregnancy loss for coffee consumption before (Pooled ES: 1.21; 95% CI: 1.01–1.43) and during pregnancy (Pooled ES: 1.26; 95% CI: 1.04–1.57), and for coffee consumption during pregnancy in case-control studies (Pooled ES: 1.20; 95% CI: 1.19–6.41). Findings from this meta-analysis demonstrated that caffeine intake during pregnancy was associated with a significantly higher risk of pregnancy loss in cohort (Pooled ES: 1.58; 95% CI: 1.23–2.01) and case-control studies (Pooled ES: 2.39; 95% CI: 1.69–3.37, P < 0.001), respectively. A dose–response analysis suggested that an increase of a cup of coffee per day during pregnancy was associated with 3% increased risk of pregnancy loss; 100 mg of caffeine per day during pregnancy was also associated with 14 and 26% increased risk of pregnancy loss in cohort and case-control studies, respectively. A non-linear dose–response association was observed between coffee intake and the risk of pregnancy loss. Conclusion This study confirms that coffee or caffeine consumption raises the risk of pregnancy loss. Researchers are encouraged to conduct more studies to explore the underlying mechanisms and active compounds in coffee and caffeine. Systematic Review Registration [www.crd.york.ac.uk/prospero/], identifier [CRD42021267731].